Impact of Topographic Steps in the Wake and Power of a Wind Turbine: Part A—Statistics - Buen Zhang; Shyuan Cheng; Fanghan Lu; Yuan Zheng; Leonardo P. Chamorro (Energies, 2020)
We experimentally explored the modulation of various forward- and backward-facing topographic steps on the wake and power output of a wind turbine model. The sharp surface changes located in the vicinity of the turbine tower consisted of steps <semantics>Δz0/dT=−0.64</semantics>, −0.42, −0.21, 0, 0.21, and 0.42, where <semantics>Δz0</semantics> is the level difference between the upwind and downwind sides of the step and <semantics>dT</semantics> is the turbine diameter. Particle image velocimetry was used to obtain the wake statistics in the wake within the streamwise distance <semantics>x/dT∈[2,</semantics> 5] and vertical span <semantics>z/dT∈[−0.7,</semantics> 0.7], where the origin is set at the rotor hub. Complementary single-point hotwire measurements were obtained in the wake along the rotor axis every <semantics>Δx/dT=1</semantics> within <semantics>x/dT∈[1,</semantics> 8]. Mean power output and its fluctuations were obtained for each of the six scenarios. The results indicate strong modulation of the steps in the wake statistics and some effect on the power output. Remarkably, the backward-facing steps induced a larger velocity deficit in the wake with respect to the base case with substantial wake deflection. In contrast, the forward-facing steps exhibited a much lower velocity deficit and negligible wake deflection. The mean flow and velocity gradients’ changes promoted distinct turbulence dynamics and, consequently, associated levels. In particular, turbulence intensity and kinematic Reynolds shear stress were enhanced and reduced with the backward- and forward-facing steps, respectively. It is worth pointing out the particular effect of the steps on the transport of the turbulence kinetic energy <semantics>TKE</semantics>. Ejections were predominant around the top tip, whereas sweeps dominated around the turbine hub height. The magnitude of these quantities was sensitive to the step height. In particular, a much weaker sweep occurred in the forward-facing steps; in addition, the flat terrain and the backward-facing step cases shared strong sweeps.